2022
DOI: 10.1002/lary.30444
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Tracheal Transplantation: A Twenty Month Follow Up

Abstract: Background: Tracheal transplantation has been considered the ideal option for the reconstruction of long-segment circumferential tracheal defects. Our group developed a technique for vascularized single-staged tracheal transplantation. Twenty months ago, we performed the first-in-human tracheal transplantation. Herein, we report a twenty-month follow-up.Methods: The recipient presented with a 9.0 cm airway tracheal stenosis and complete cricoid stenosis. The patient previously failed six major conventional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Interestingly, FISH cytogenetic assays demonstrated initially a rapid increase in recipient‐derived cells, which represented 98.9% of epithelial cells by day 111 from transplantation. However, the percentage of recipient‐derived epithelial cells declined to only .8% after 455 days from transplantation 31 . FISH cytogenetic assay was also reported by Delaere et al.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, FISH cytogenetic assays demonstrated initially a rapid increase in recipient‐derived cells, which represented 98.9% of epithelial cells by day 111 from transplantation. However, the percentage of recipient‐derived epithelial cells declined to only .8% after 455 days from transplantation 31 . FISH cytogenetic assay was also reported by Delaere et al.…”
Section: Resultssupporting
confidence: 58%
“…However, the percentage of recipient-derived epithelial cells declined to only .8% after 455 days from transplantation. 31 FISH cytogenetic assay was also reported by Delaere et al in their first patient, after withdrawal of immunosuppressive therapy. At the time of orthotopic transplantation, the allograft was trimmed to the desired length, and redundant tissue was used for cytogenetic analysis, which demonstrated that the respiratory epithelium in the anterior part of the graft was of donor's origin.…”
Section: Postoperative Assessmentssupporting
confidence: 57%
“…5 The patient has subsequently been decannulated and remains breathing and phonating without difficulty 2 years after surgery. 6 We have shown previously that after an initial epithelial injury there was a degree of epithelial repopulation that provided functional mucociliary clearance on a blue dye test. 5 Fascinatingly, as seen in animal models, the epithelial repopulation was in part recipient-derived.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, this would coincide with the drop in recipient-derived epithelium seen by POD 111. 6 Additionally the ciliated epithelial cells present contained some serous granules which suggest that some of the ciliated epithelium were derived from serous cells precursors as well. Ultimately 200-400 days after surgery, normal ciliated epithelium and mucous cells appear without signs of chronic inflammation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation